Inhibition of STAT5A promotes osteogenesis by DLX5 regulation. Issue 11 (November 2018) - Lee, Kyoung-Mi; Park, Kwang; Hwang, Ji; Lee, Moses; Yoon, Dong; Ryu, Hyun; Jung, Ho; Park, Ki; Kim, Jihyun; Park, Sahng; Kim, Sung-Hwan; Chun, Yong-Min; et al.
Abstract The regulation of osteogenesis is important for bone formation and fracture healing. Despite advances in understanding the molecular mechanisms of osteogenesis, crucial modulators in this process are not well-characterized. Here we demonstrate that suppression of signal transducer and activator of transcription 5A (STAT5A) activates distal-less homeobox 5 (DLX5) in human bone marrow-derived stromal cells (hBMSCs) and enhances osteogenesis in vitro and in vivo. We show that STAT5A negatively regulates expression ofDlx5 in vitro and that STAT5A deletion results in increased trabecular and cortical bone mass and bone mineral density in mice. Additionally, STAT5A deletion prevents age-related bone loss. In a murine fracture model, STAT5A deletion was found to significantly enhance bone remodeling by stimulating the formation of a fracture callus. Our findings indicate that STAT5A inhibition enhances bone formation by promoting osteogenesis of BMSCs.